PERBAIKAN KESEIMBANGAN LlINI PRODUKSI PERAKITAN ELEKTRONIK PT ’X’ DIDUKUNG SISTEM SIMULASI - Primasanti, Yunita; Kohar Sulistyadi (Jurnal Rekavasi, 2024)
Improving of assignment line balancing at work stations must be use to get increasing effisiency production line. The effisiency of production line can be represented by minimum number of worker to put in production, and minium idle time. The aim of research is to find improving of assembly production line and to achieve the production target into simulation system in line balancing. Line CY.14-XX is one of the production line that proude television with capacity 190 unit per hour. Time work have been measure by time study method. The first condition efficiency of production line is 70 percent with idle time is 191 second or 29 percent, and number of operating workers for producing television using 40 operator. The result of simulation system in production line shows efficiency of production line increase 81 percent with idle time is 115 seconds or 19 percen, and number of operating workers for producting television decreasing 4 operators or using 36 operators. Pursuant on simulation system result that the proposal of improvement line of balancing electronic assembly can be applied to real production system.